2021
DOI: 10.1002/app.51756
|View full text |Cite
|
Sign up to set email alerts
|

A study of the properties and efficacy of microparticles based on P(3HB) and P(3HB/3HV) loaded with herbicides

Abstract: The wide use of pesticides in agriculture has caused uncontrolled distribution of these chemicals in the environment, calling for the development and investigation of new environmentally friendly formulations, which would reduce human impact on nature. In the present study, the metribuzin (MET), tribenuron-methyl (TBM), and fenoxaprop-P-ethyl (FPE) herbicides were encapsulated in microparticles of degradable microbial polymerspolyhydroxyalkanoates (PHAs)of two typespoly-3-hydroxybutyrate [P(3HB)] and poly(3-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This result could be attributed to the lack of aqueous solubility shown by this aromatic acylhydrazone, which could hinder its translocation inside the weed. A related study dealing with the bioactivity of different herbicide microcapsules, including metribuzin, indicated that herbicidal activity increases with the herbicide solubility [ 56 ]. However, the application of A24 formulations (aliphatic acylhydrazone 24 ) at both doses produced significant decreases in rapeseed biomass compared to the control treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result could be attributed to the lack of aqueous solubility shown by this aromatic acylhydrazone, which could hinder its translocation inside the weed. A related study dealing with the bioactivity of different herbicide microcapsules, including metribuzin, indicated that herbicidal activity increases with the herbicide solubility [ 56 ]. However, the application of A24 formulations (aliphatic acylhydrazone 24 ) at both doses produced significant decreases in rapeseed biomass compared to the control treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An application similar to drug delivery was reported by R. Vijayamma et al [84], where a herbicide delivery system composed of P(3HB) and P(3HB/3HV) was tested. Metribuzin, a herbicide derived from 1,2,4-triazine, demonstrated the best release results with an index of 44-48%, and in the tests carried out during the growth of the plant, Elsholtzia ciliata microparticles loaded with metribuzin and tribenuron-methyl demonstrated the best result.…”
Section: Other Applications In Medicinementioning
confidence: 88%
“…The formulation of a plethora of PHA-based materials, i.e., copolymers, physical and/or meltreactive blending with tailored polymers, and the addition of organic and inorganic fillers and plasticizers, has led to the improvement of mechanical features, wide processability windows, and enhanced stability and permeability performances [2]. So far, owing to its special polymer features, PHA with diverse structures and properties has been exploited in several application fields, i.e., as bioplastics for food packaging [3], in tissue engineering for biomedical implants and drug delivery carriers [5], and in the agriculture sector for the controlled delivery of herbicides [6].…”
Section: Introductionmentioning
confidence: 99%